An assessment of risk management's mediating effect on financial innovation and bank's performance: A study of selected ASEAN-5 listed commercial banks from 2018-2020 - Nisce, Raphael Gerardo (Animo Repository, 2022)
Financial innovation has gained significance as a result of the changes it has brought to the banking sector after the 2007/2008 crisis and the more recent COVID-19 pandemic. These events have introduced new challenges and concerns in the banking sector which highlights the critical need to understand the relationship between financial innovation, risk management, and bank performance in order to determine effective banking strategies moving forward. This study aims to uncover the potential benefits and challenges that the banking sector may face in the near future by examining the mediating effect of risk management on the relationship between financial innovation and bank performance among selected publicly-listed commercial banks in the ASEAN-5 between 2018 and 2020. Statistical mediation analysis adopting the structural equation model framework was conducted. The findings indicate that when analyzed individually, financial innovation measured through count of digital transactions have a positive, significant relationship with bank profitability ratios as well as a significant relationship with risk management measures, with a positive effect on capital adequacy, market risk-weighted assets, and operational risk-weighted assets, and a negative relationship with credit risk-weighted assets. The results of the final structural equation model however indicate that financial innovation has a significant positive relationship with risk management but risk management has an insignificant relationship with bank performance and thus, risk management has no partial mediation effect on the relationship between financial innovation and bank performance.